Pengaruh Stigma Sosial, Revitalisasi Pasar, Dukungan Pemerintah dan Akses Fasilitas Terhadap Kepuasan Pedagang di Pasar Mama-Mama Papua Kota Jayapura - Hasmawati Hasmawati; Ike Kusdyah Rachmawati; Yunus Handoko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effects of social stigma, market revitalization, government support, and facility access on the satisfaction of Indigenous Papuan women traders at the Mama-Mama Papua Market in Jayapura City. A quantitative approach was employed using a survey method with active traders as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results indicate that market revitalization and facility access have positive and significant partial effects on trader satisfaction, while social stigma and government support do not show significant partial effects. Nevertheless, all variables simultaneously have a significant effect on trader satisfaction, with facility access emerging as the most dominant factor. These findings highlight that satisfaction in affirmative traditional markets is primarily shaped by structural and functional conditions directly experienced in daily trading activities. The study offers policy-relevant insights for managing people-centered traditional markets grounded in social justice and local wisdom.